2016
DOI: 10.3389/fendo.2016.00170
|View full text |Cite
|
Sign up to set email alerts
|

GnIH Control of Feeding and Reproductive Behaviors

Abstract: In 2000, Tsutsui and colleagues discovered a neuropeptide gonadotropin-inhibitory hormone (GnIH) that inhibits gonadotropin release in birds. Subsequently, extensive studies during the last 15 years have demonstrated that GnIH is a key neurohormone that regulates reproduction in vertebrates, acting in the brain and on the pituitary to modulate reproduction and reproductive behavior. On the other hand, deprivation of food and other metabolic challenges inhibit the reproductive axis as well as sexual motivation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 145 publications
1
48
1
Order By: Relevance
“…Because the identified neuropeptides possess LPXRFamide (X = L or Q) motif at their C-termini, the mammalian GnIH orthologous gene and peptide are called Rfrp and RFRP-3, respectively. GnIH/RFRP-3 neurons project to the median eminence in birds and female sheep and suppress the secretion and synthesis of gonadotropin via GnIH/RFRP-3 receptor GPR147 under both in vivo and in vitro conditions in male birds, female rats, and female sheep (19, 22, 24, 25). GnIH/RFRP-3 neurons also project to GnRH neurons and inhibit their activity via GPR147 in birds and mammals (22, 26, 27).…”
Section: The Role Of Gnih/rfrp-3 In Stress-induced Suppression Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…Because the identified neuropeptides possess LPXRFamide (X = L or Q) motif at their C-termini, the mammalian GnIH orthologous gene and peptide are called Rfrp and RFRP-3, respectively. GnIH/RFRP-3 neurons project to the median eminence in birds and female sheep and suppress the secretion and synthesis of gonadotropin via GnIH/RFRP-3 receptor GPR147 under both in vivo and in vitro conditions in male birds, female rats, and female sheep (19, 22, 24, 25). GnIH/RFRP-3 neurons also project to GnRH neurons and inhibit their activity via GPR147 in birds and mammals (22, 26, 27).…”
Section: The Role Of Gnih/rfrp-3 In Stress-induced Suppression Of Thementioning
confidence: 99%
“…Therefore, GnIH/RFRP-3 inhibits gonadotropin secretion and synthesis through direct and indirect actions on the pituitary. It has been shown that GnIH/RFRP-3 inhibits GnRH-elicited gonadotropin release and decreases LH pulse amplitude in female sheep (22, 24), and GnIH/RFRP-3 activity is decreased by high estradiol (E2) concentrations at the time of the GnRH/LH surge in female hamsters (Figure 1A) (20, 22). Similarly, elevated estrogen lowers Rfrp mRNA levels in male and female mice (28).…”
Section: The Role Of Gnih/rfrp-3 In Stress-induced Suppression Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…As this neuropeptide was the first hypothalamic factor that was found to suppress gonadotropin release, it was named GnIH based on its biological activity. GnIH molecules were subsequently identified in other vertebrates, mammals, primates, and humans [68][69][70]. The mammalian GnIH orthologous gene and peptide are named Rfrp and RFRP-3, respectively, because the neuropeptide possesses the LPXRFamide (X = L or Q) motif in its C-terminus.…”
Section: Physiological Roles Of Kisspeptin and Gnih/rfrp-3mentioning
confidence: 99%
“…Hypothalamic GnIH/ RFRP-3 neurons are mainly located in the paraventricular nucleus in birds and the dorsomedial hypothalamic area in mammals [71]. GnIH/RFRP-3 neurons project to the median eminence in birds and female sheep, and suppress the synthesis and secretion of gonadotropins at the pituitary level via the GnIH/RFRP-3 receptor GPR147 under both in vivo and in vitro conditions in male birds, female rats, and female sheep [17,26,69,72]. In addition, GnIH/RFRP-3 neurons project to GnRH neurons in the hypothalamus and suppress their activity via GPR147 in mammals and birds [23,26,73].…”
Section: Physiological Roles Of Kisspeptin and Gnih/rfrp-3mentioning
confidence: 99%